Subjective well-being's alterations as risk factors for major depressive disorder during the perimenopause onset: an analytical cross-sectional study amongst Mexican women residing in Guadalajara, Jalisco - Adrián Enrique Hernández-Muñoz; Ana Méndez-Magaña; Ana Lilia Fletes-Rayas; Miguel A. Rangel; Lenin Torres García; José de Jesús López-Jiménez (BMC, 2022)
Abstract Background Subjective well-being (SWB) can be defined as a self-report evaluation that reflects the satisfaction, and emotional level, over several social and personal indicators. Alterations in these indicators could become risk factors (RF) for major depressive disorder (MDD), but this association has not been studied at women's life stages such as the perimenopause onset, despite its increasing prevalence for depressive symptomatology. Therefore, the aim of this study was to identify if SWB's alterations determine RF for MDD during the perimenopause. Methods An analytical cross-sectional study was realized in 252 Mexican women with perimenopause's age range (48 ± 1.7) and menopausal symptomatology, treated on Medical Units belonging to Jalisco's 13th Health-Region. We applied the INEGI's Basic Self-Reported Wellbeing Survey (BIARE) that measured 30 SWB's indicators. To identify MDD's presence, the Beck's Depression Inventory-II (BDI-II) was applied. The sample was studied with associative analysis, along with logistic regression models, to determine adjusted odds ratio (aOR) and corresponding 95% confidence interval (95% CI). Results Trough the BDI-II we identified 40.5% women with MDD. When compared with the undepressed group we found lower scores in all the SWB's indicators, along with significant associations for depressive symptomatology. However, the logistic regression allowed us to identify significant RF when the women specifically reported personal life-dissatisfaction (aOR 9.6, 95% CI 1.90-17.68), emotional imbalances between happiness/sadness (aOR 7.1, 95% CI 1.49-13.57) and concentration/boredom (aOR 6.7, 95% CI 1.43-13.48); free-time dissatisfaction (aOR 5.5, 95% CI 1.17-5.70), public security unconformity (aOR 5.4, 95% CI 2.20-11.3), and sense of purposelessness (aOR 4.2, 95% CI 1.07-19.41). Conclusion The main objective of the study was to determine if SWB's alterations are RF for depressive symptomatology, finding that social indicators with low scores are associated with MDD by means of aOR -Which were higher when compared to international research studies. Considering this, we suggest that more studies should be implemented, in order to understand and correctly attend the women's social conditions during their perimenopause transition.